2021
DOI: 10.3168/jds.2020-19665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fat supplements containing different levels of palmitic and stearic acid on milk production and fatty acid digestibility in lactating dairy cows

Abstract: Fat supplements based on palmitic acid (PA) or stearic acid (SA) are expected to have different effects on milk production and nutrient metabolism in lactating dairy cows. In this study, the effects of prilled fat supplements containing different levels of PA and SA were tested in 12 high-producing multiparous cows (pretrial milk yield = 53.4 ± 8.7 kg/d; mean ± SD) arranged in a 4 × 4 Latin square design with 21-d periods. Treatments were control (CON; no supplemental fat), an enriched PA supplement (HP; 91% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Preformed FA increased with most diets evaluated in our study (Groups 1, 2, and 3). These findings are consistent with those reported by dos Santos Neto et al [ 12 ] and Shepardson and Harvatine [ 22 ]. However, other studies indicate that sources with high SFA content do not affect the synthesis of preformed FA in milk [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Preformed FA increased with most diets evaluated in our study (Groups 1, 2, and 3). These findings are consistent with those reported by dos Santos Neto et al [ 12 ] and Shepardson and Harvatine [ 22 ]. However, other studies indicate that sources with high SFA content do not affect the synthesis of preformed FA in milk [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 94%
“…In general, it is known that lipid supplementation in dairy cow diets increases milk production [ 12 , 13 , 14 ]. However, there are reports suggesting that certain lipid sources have no effect on milk production [ 22 , 23 , 24 ]. Consistent with these findings, our study showed that diets rich in UFA had no effect on milk production.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of an almost pure C18:0 supplement (>90% C18:0) at 1.92% (Piantoni et al, 2015) and 2.30% (Boerman et al, 2017) diet DM reduced FA digestibility of lactating dairy cows by 20 and 28 percentage units, respectively. When included at 1.95% in the diet DM, a C18: 0 -enriched supplement (92.6% C18:0) decreased total and 16-carbon FA absorption compared with a C16: 0 -enriched supplement (91.0% C16:0; Shepardson and Harvatine, 2021). Our recent meta-analysis observed that diets containing mixed C16:0 + C18:0 supplements decreased FA digestibility by 5.20 percentage units compared with control diets not supplemented with FA, whereas diets with C16: 0 -enriched supplements had no effect (dos Santos Neto et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that PA promoted ARID3A protein expression and SREBP1 expression and maturation in HC11 cells in a dose‐dependent manner. It is well known that long chain fatty acids such as PA and stearic acid can promote milk fat synthesis in mammary epithelial cells (Jin et al, 2022; Shepardson & Harvatine, 2021). We observed that high concentration of PA has inhibitory effects on SREBP1 expression and maturation, in agreement with previous reports that high concentration of fatty acids may have cytotoxic effects and induce apoptosis (Ng & Say, 2018; de Sousa Andrade et al, 2005).…”
Section: Discussionmentioning
confidence: 99%